THE MEDIATING ROLE OF SATISFACTION TOWARD REMUNERATION SYSTEM: POS RELATED TO PERFORMANCE - Hunik Sri Runing Sawitri; Salamah Wahyuni; Anastasia Riani Suprapti; Desy Mayasari (EKUITAS (Jurnal Ekonomi dan Keuangan), 2018)
This study aims to test the mediating role of satisfaction toward remuneration system on the effect of supervisor support on performance. This study is conducted to 298 people who work as academic staff and administrative staffs. The samples are selected using stratified random sampling. It is hypothesized that, 1) supervisor support affects the satisfaction toward remuneration system, 2) satisfaction toward remuneration system affects employee performance, 3) supervisor support affects employee performance, and 4) satisfaction toward remuneration system mediates the effect of supervisor support on employee performance. The result of regression analysis shows that supervisor support positively and significantly affects satisfaction toward remuneration system. Satisfaction toward remuneration system has positive and significant effect on performance, but supervisor support has no significant effect on performance. The testing on mediation effect shows that satisfaction toward remuneration system fully mediates the effect of supervisor support on employee performance.